8(-2m-7)+8(-5+m)=4m-6m

Simple and best practice solution for 8(-2m-7)+8(-5+m)=4m-6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(-2m-7)+8(-5+m)=4m-6m equation:


Simplifying
8(-2m + -7) + 8(-5 + m) = 4m + -6m

Reorder the terms:
8(-7 + -2m) + 8(-5 + m) = 4m + -6m
(-7 * 8 + -2m * 8) + 8(-5 + m) = 4m + -6m
(-56 + -16m) + 8(-5 + m) = 4m + -6m
-56 + -16m + (-5 * 8 + m * 8) = 4m + -6m
-56 + -16m + (-40 + 8m) = 4m + -6m

Reorder the terms:
-56 + -40 + -16m + 8m = 4m + -6m

Combine like terms: -56 + -40 = -96
-96 + -16m + 8m = 4m + -6m

Combine like terms: -16m + 8m = -8m
-96 + -8m = 4m + -6m

Combine like terms: 4m + -6m = -2m
-96 + -8m = -2m

Solving
-96 + -8m = -2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '2m' to each side of the equation.
-96 + -8m + 2m = -2m + 2m

Combine like terms: -8m + 2m = -6m
-96 + -6m = -2m + 2m

Combine like terms: -2m + 2m = 0
-96 + -6m = 0

Add '96' to each side of the equation.
-96 + 96 + -6m = 0 + 96

Combine like terms: -96 + 96 = 0
0 + -6m = 0 + 96
-6m = 0 + 96

Combine like terms: 0 + 96 = 96
-6m = 96

Divide each side by '-6'.
m = -16

Simplifying
m = -16

See similar equations:

| 3z+2(6-z)=-(z-1)+1 | | 3a-10=-25 | | 28*x=(4x-2)*7 | | 5-8x+x=40 | | d(3d-15)=0 | | Y=.5+8 | | -8m-[2(10-5m)+15]=9m | | 45a^4b^3/15a^4b^2 | | r^2+81=r^2+6r+9 | | 2(7c-1)-18=12c+2 | | 7.4X=-52.54 | | -4.6X+1.1=-21.9 | | 2(c-1)-18=12c+2 | | 6sin^2+5cos=2 | | (2/3)^5= | | X-1=9.58 | | 18-(4m+4)=4+2m-14 | | 98/6 | | 2x-20=5x+9 | | 12x+0.5x+x=40 | | 2(f-8)=-30 | | 10(s-5)=-152 | | lnx=(1/8) | | 4k^2=9k | | 4(t+3)=-4 | | 7(25x+2)=0 | | 51.20=128-r*128 | | (7t+2)(t^2-5t-3)=0 | | 7(x+49)+28=14x-42+7x | | 3z^2-x-6=0 | | 2x=0.8x+54 | | 2x=0.8+54 |

Equations solver categories